Feed supplementation and weight change, milk yield and post-partum oestrus in Desi cows - Alam, MGS; Rahman, MA; Khatun, M; Ahmed, JU (Bangladesh Veterinarian, 2010)
A feeding trial was performed with 16 multiparous lactating Desi (indigenous) cows for 32 weeks to evaluate the effects of dhaincha (Sesbania aculeata) and ipil-ipil (Leucaena leucocephala) as alternative sources of protein together with urea-treated straw, fish meal, green grass and urea molasses mineral block (UMMB) on body weight, milk yield and resumption of ovarian cyclicity after parturition. Cows were grouped into four and supplied four diets. Cows in groups B (dhaincha, ipil-ipil, treated straw, fish meal and common salt), group C (UMMB and green grass), and group A (treated straw, fish meal and common salt) gained body weight 20.7 ± 2.1, 17.2 ± 1.3 and 15.4 ± 3.6 kg, respectively, over a period of 32 weeks. Non-supplemented cows (group D) lost body weight an average of 12.5 ± 5.4 kg. Among the supplemented cows, significantly (P<0.05) better weight gain was observed in group B than groups C and A. The difference in weight gain between B and C, and C and A were not significant (P>0.05). Significantly (P<0.01) higher milk yield was observed in groups B, C and A than in D. There were no significant (P>0.05) differences in milk yield between groups B, A and C. The animals of group C, B and A expressed behavioural oestrus 84-190 (149.0 ± 46.3), 131-220 (178.0 ± 32.0) and 179-218 (200.5 ± 14.0) days postpartum, respectively, these were not significantly (P>0.05) different. None of the cows in group D manifested oestrus during the study period. It is suggested that feed supplementation during lactation in cows stimulates ovarian cyclicity earlier. Dhaincha and ipil-ipil could be used as alternative sources of protein for ruminants, which may result in better weight gain, milk yield and reproductive performance during postpartum period in indigenous cows. DOI: 10.3329/bvet.v26i2.4949 Bangl. vet. 2009. Vol. 26, No. 2, 39-47